A double paradise: language, subject and emotiveness in modernist poetry - Valencia Sala, Gladys (2015)
The author proposes a reading that will analyze historical documents from modernist journals, which will be seen as theoretical documents in which we can recognize indications that modernist poetry was conceived as an artifact arising from criticism, theory and even method. It could be said that modern criticism draws some maps of what should be considered as a method of poetic knowledge and representation. The concept of sensitivity proposed by Gutiérrez Nájera, in his essay by installments “El arte y el materialismo”, constitutes a synthesis of the work of a wide circle of intellectuals who conceived the work of art as a scenario in which the renovation of sensitivity is possible in the context of a conflictive experience of emancipation. In this sense, Darío warns that the reader should not be enraptured by the landscape created by the modernist poet; rather he should discover the exercise of dissociation between sensitivity and reality to which the poet who enters the discourse of form is invited.